NVIDIA HIGH PERFORMANCE COMPUTING SOLUTION CUDA APPLICATION FOR IMAGE PROCESSING - Stankevičš, Jānis; Kodors, Sergejs (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2018)
The goal of this research report is to compare the program execution times using the Central Processing Unit and NVIDIA’s high throughput solution CUDA to execute the program on the Graphic Processing Unit. The programs will run an algorithm to convert a raster image into dotted half-tone. CUDA`s programming model allows programmers to run their programs on a parallel GPU architecture consisting of several blocks of threads that are being ran in parallel. This dynamic technology allows to further decrease the time it takes to run a program, by simply adding more GPU’s or upgrading the existing one The research experiment concluded that NVIDIA solution is faster than using usual CPU serial code